TANJUNG PURA INTERCHANGE BRIDGE PILLAR ANALYSIS BASED ON SP COLOMN VALUE - Gede Suartana; I Nengah Sinarta; I Wayan Gde Erick Triswandana (Journal of Infrastructure Planning and Engineering, 2024)
The Tanjung Pura interchange overpass bridge, a critical connector road on the Trans Sumatra Toll Road, currently utilizes wall-type pillars that have limitations in seismic performance and construction efficiency. This study aims to redesign the bridge pillars from a wall-type to a portal-type configuration to improve structural safety and optimize the design. The redesign process involves several key steps, including data collection through literature review and documentation from project stakeholders, structural modeling using SAP2000 v.20 software incorporating the redesigned portal-type pillars with optimized dimensions and reinforcement arrangements, load analysis considering various load combinations based on Indonesian bridge design codes and standards, and capacity evaluation using SP Column v.7 software to assess the structural adequacy and safety of the redesigned pillars. The portal-type pillars, with dimensions of 1500 mm × 2500 mm and 50D32 main reinforcement, along with additional leg reinforcement in the plastic hinge regions, demonstrated improved seismic performance and constructability compared to the original wall-type design, with a maximum capacity ratio of 0.20 indicating sufficient reserve capacity and safety margin. The successful redesign of the Tanjung Pura interchange overpass bridge pillars highlights the potential for optimizing bridge structures to enhance safety, efficiency, and economy, serving as a valuable reference for future bridge rehabilitation and redesign projects.